Neuronal HIF-1α and HIF-2α deficiency improves neuronal survival and sensorimotor function in the early acute phase after ischemic stroke - Barteczek, Philipp; Li, Lexiao; Ernst, Anne-Sophie; Böhler, Laura-Inés; Marti, Hugo; Kunze, Reiner (Journal of critical care, 2017)
Hypoxia-inducible factors mediate adaptive responses to ischemia, among others, by induction of anti- and pro-survival genes. Thus, the impact of HIF on neuronal survival upon stroke is controversial. Therefore, neuron-specific knockout mice deficient for Hif1a and Hif2a were exposed to inspiratory hypoxia or ischemia-reperfusion injury. Both Hif1a- and Hif2a-deficient mice showed no altered infarct and edema size, suggesting that both HIF-α subunits might compensate for each other. Accordingly, hypoxic HIF-target gene regulation was marginally affected with exception of anti-survival Bnip3 and pro-survival erythropoietin. In the early acute stage upon stroke, Hif1a/Hif2a double knockout mice exhibited significantly reduced expression of the anti-survival Bnip3, Bnip3L, and Pmaip1. Accordingly, global cell death and edema were significantly reduced upon 24 h but not 72 h reperfusion. Behavioral assessment indicated that Hif1a/Hif2a-deficient mice initially performed better, but became significantly more impaired after 72 h accompanied by increased apoptosis and reduced angiogenesis. Our findings suggest that in neurons HIF-1 and HIF-2 have redundant functions for cellular survival under ischemic conditions. By contrast, lack of anti-survival factors in Hif1a/Hif2a-deficient mice might protect from early acute neuronal cell death and neurological impairment, indicating a benefit of HIF-pathway inhibition in neurons in the very acute phase after ischemic stroke.
Received: July 21, 2015; Revisions received: October 30, 2015; Accepted: December 07, 2015; First Published January 8, 2016
Gesehen am 01.10.2018